Population Health Intervention Implementation Among Migrants With Precarious Status in Montreal: Underlying Theory and Key Challenges. (May 2020) - Belaid, Loubna; Benoit, Magalie; Kaur, Navdeep; Lili, Azari; Ridde, Valery
The purpose of this study is to describe the underlying theory and the challenges involved in implementing an intervention to access health care services for migrants with precarious status (MPS) in Montreal. The description of the underlying theory of the intervention was based on a documentary analysis and a workshop with clinicians ( n = 9). The challenges were identified through concept mapping ( n = 28) and in-depth interviews ( n = 13). The results of the study indicated that the aims of the intervention were to provide access to health care to MPS primarily to avoid any further health status deterioration. The most significant challenges identified were sustainable funding resources and improved access to care and protection for MPS. The interviews indicated that MPS are difficult to reach out; public health care system rules are unclear; resource constraints make it difficult to provide adequate and continuing care; and advocacy activities are difficult to organize.